Stimuli responsive carboxyl rich carbon photonic ball ink via template assisted light thermal dehydration of monosaccharides - Shin Geun Park; Yong Seok Kim; Hyunjung Lee; Wonmok Lee (Scientific Reports)
Abstract In this study, we investigated a color-tunable carboxyl-rich carbon inverse photonic ball (CIPB) ink, which was fabricated using a polymeric photonic ball (PB) as a template, with characteristic self-assembled opalline structures from monodisperse polystyrene (PS) microspheres. The PBs were prepared on a large scale via an optimized diffusive drying method using an aqueous dispersion of polystyrene microspheres. Via acid-catalyzed thermal dehydration of monosaccharides within the interstitial space of PB followed by template removal, iridescent CIPB, which is insoluble in water or organic solvents because the crosslinked structure is similar to a naturally occurring humin, was obtained. The use of PS microspheres of different sizes for the preparation of the respective PBs resulted in CIPBs with different structural colors. Optical characterization revealed that the individual CIPB particles exhibit specific colors on the basis of the angular dependence of the Bragg condition for each particle. The overall structural color of the CIPB ink was sensitively tuned by changing dispersing media with different indices of refraction. Spectroscopic analysis confirmed the presence of carboxyl groups within CIPB due to the light thermal condensation of sugar, and the osmotic swelling/deswelling of the charged CIPB at pH values above/below the pKa of the bound carboxylate drove the reversible pH-responsive changes in structural color, indicating the promising applicability of CIPB as a colorimetric chemical sensor.